The impact of exercise motives on adolescents' sustained use of wearable technology. Issue 7 (19th May 2021) - Deranek, Kimberly; Hewitt, Barbara; Gudi, Arvind; McLeod, Alexander
ABSTRACT: Wearable technology has become extremely prevalent; however, adoption and sustained long-term use are still issues. Understanding behaviours associated with the use and adoption of a wearable device is important to understand if the usage of the device promotes health and wellness. This study investigated the influence that extrinsic and intrinsic exercise motives have on the sustained use of wearable technology amongst adolescents. Fifty-nine high school students (juniors and seniors) enrolled in the study. Participants received Fitbits as a means of exercise persuasion. At the beginning of the study, participants completed an Exercise Motivations Inventory [Markland, D., and D. K. Ingledew. 1997. "The Measurement of Exercise Motives: Factorial Validity and Invariance Across Gender of a Revised Exercise Motivations Inventory." British Journal of Health Psychology 2: 361–376] establishing motives and baseline exercise behaviours. Use of the Fitbit enabled the electronic collection of each participant's daily activities over a period of three months. The results revealed a relationship between three intrinsic exercise motives with technology use; affiliation, revitalisation, and health pressures. There was also a significant difference between participants who complied versus those who did not across two of the exercise motives affiliation and revitalisation.